Pengaruh Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. SIE - Intan Vandini; Aji Tuhagana; Dwi Epty Hidayaty (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of work discipline and job satisfaction on employee performance, both partially and simultaneously, at PT. SIE. The research method used is a quantitative descriptive survey approach. The population in this study was all 80 employees of the MW division of PT. SIE, who also served as the research sample using a saturated sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed using SPSS version 25 software through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results show that work discipline has a positive and significant effect on employee performance, job satisfaction also has a positive and significant effect on employee performance, and both work discipline and job satisfaction simultaneously have a significant effect on employee performance at PT. SIE. In conclusion, consistently improving work discipline and employee job satisfaction can improve employee performance. Therefore, companies need to consider both factors as a strategy to improve the achievement of organizational goals.   Keywords: Work Discipline, Job Satisfaction, Employee Performance, Human Resources